(untitled) (Bangladesh Journal of Botany, 2019)
It was intended to investigate the biological activities of different solvent extracts of the fruiting bodies of Calocybe indica (P & C). The bioactive compounds were extracted using acetone, methanol, and hot water. The antioxidant activities of three different extracts at 0.5-20.0 mg/ml of C. indica on β-carotene-linoleic acid ranged from 65.83 - 92.56, 62.79 - 93.06 and 61.42 - 92.12%, respectively. The highest (2.825) reducing power inhibition was recorded in methanolic extract, while the lowest (2.332) was in hot water at the concentration of 8 mg/ml. The free radicle scavenging activity was more pronounced in methanolic extract. Chelating effect of C. indica was significantly strong as compared to positive control. The xanthine oxidase and tyrosinase inhibitory activity of the acetone, methanol, and hot water extracts of C. indica increased with increasing concentration. Thirteen phenolic compounds i.e. biochanin-A, caffeic acid, chlorogenic acid, ferulic acid, formononetin, gallic acid, hesperetin, homogentisic acid, naringenin, naringin, protocatechuic acid, resveratrol and vanillin were detected from acetonitrile-hydrochloric acid extract. The result indicated that the maximum and minimum concentrations were recorded for gallic acid (29 μg/g) and formononetin (10 μg/g). Thus, it could be suggested that C. indica has the potential to be used as antioxidant and tyrosinase protection system of the human body against oxidative damage and other complications.